Modèles de politique économique multirégionale basés sur l’analyse d’attraction - Paelinck, J. (L'Actualité économique, 1973)
AbstractClassical regional and multiregional models were limited in scope and usefulness as they failed to integrate explicitly locational factors, especially on the supply side.Two types of models, the attraction model and the profile model, allow to treat this problem adequately. They are presented in their most recent formulation that improves on earlier versions.Regional spill-over effects are underlined as being essential in the understanding of multiregional growth patterns; they are explicitly integrated in the aforementioned models, which thus take care of market potentials and clustering through spread of external economies.The models mentioned are currently applied to Germany, Spain, and the regions of the enlarged Common Market (project "FLEUR").